Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.iecr.8b03597
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Key Factors of NO Oxidation Using O3: The Oxidation Product Composition and Oxidation Selectivity

Abstract: NO oxidation using O3 is studied, including the product composition under different conditions and the oxidation selectivity in complex flue gas. The O3/NO molar ratio determines the type of oxidation products. N2O5 is generated when the O3/NO molar ratio is greater than 1, and the N2O5 yield increases with the improvement of the O3/NO molar ratio. High temperature leads to the decomposition of NO3 and the decrease of the N2O5 yield. When NO3 decomposition is caused in the high-temperature region, the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 41 publications
2
18
1
Order By: Relevance
“…When the flue gas temperature was 150 °C, the O 3 decomposition rate increased from 17.4 to 21.3% with the increase of the initial O 3 concentration from 100 to 400 ppm. The result implied that ozone was very unstable at high temperatures, which agreed well with the previous study . It was obvious that, when ozone was injected in hot flue gas at a temperature higher than 150 °C, a large part of the ozone oxidant would be lost without making contributions to oxidize NO x .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…When the flue gas temperature was 150 °C, the O 3 decomposition rate increased from 17.4 to 21.3% with the increase of the initial O 3 concentration from 100 to 400 ppm. The result implied that ozone was very unstable at high temperatures, which agreed well with the previous study . It was obvious that, when ozone was injected in hot flue gas at a temperature higher than 150 °C, a large part of the ozone oxidant would be lost without making contributions to oxidize NO x .…”
Section: Resultssupporting
confidence: 89%
“…The result implied that ozone was very unstable at high temperatures, which agreed well with the previous study. 19 It was obvious that, when ozone was injected in hot flue gas at a temperature higher than 150 °C, a large part of the ozone oxidant would be lost without making contributions to oxidize NO x . 23 Therefore, it was necessary to control exhaust gas temperature below 150 °C in order to obtain a high utilization of the ozone oxidant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the oxidation temperature, a similar phenomenon was observed in our previous research. 38 The results showed that the N 2 O 5 yield first increased and then decreased with the increase of oxidation temperature, reaching the highest value at 90 °C for all O 3 /NO > 1. When the temperature of gas was higher than 90 °C, the N 2 O 5 yield decreased very rapidly.…”
Section: Resultsmentioning
confidence: 90%
“…Nitrogen oxide (NO x ), one of the main precursors of photochemical smog and haze pollution, causes great harm to the ecosystem and human lives [1,2]. Many strategies have been developed for NO x abatements from the stationary emission sources, including selective catalytic reduction (SCR) [3,4], selective non-catalytic reduction (SNCR) [5,6], activated carbon denitration [7,8], and oxidation-absorption method [9,10]. Among those methods, SCR technology has attracted extensive attention for being the most efficient strategy for NO removal [11].…”
Section: Introductionmentioning
confidence: 99%